La falta de punición del abandono a adultos mayores, afecta al derecho del buen vivir tipificado en la constitución de la república del Ecuador. - Villalta Abad, Deyvi Francisco (2011)
The development of this research in the study of non-contemplation in the Criminal Code of the abandonment of the elderly, a penalty that leads to the effective protection, protection of the State in protecting the elderly, the social sector to be respected, especially the rights contained in the Constitution of the Republic, studying and improving the regulatory regime to ensure the protection of the elderly, this is the right to physical and psychological integrity of the elderly people . In this study we analyzed in detail, the abandonment of the elderly, the re victimized, violates human rights, impunity and cause generates responsibility and duty to repair state, which generates a relational matrix between the guarantees of good living, their transgressions and elements of the crime and who founded a draft law amending the law of the elderly, the Criminal Code and criminal Procedure Code, including the constitutional standards for resolving pro older anomie, ensure human dignity, the right to good life and fundamental rights of this group of priority, to prevent their victimization, punish perpetrators and prevent state liability and redress.